2014
DOI: 10.4995/wrs.2014.1677
|View full text |Cite
|
Sign up to set email alerts
|

Impact of royal jelly to improve reproductive performance of male rabbits under hot summer conditions

Abstract: To alleviate the deleterious effect of heat stress during summer conditions on male rabbits' reproduction, 40 V Line adult rabbit bucks (on av. 8 mo old) were divided into 4 experimental groups and exposed to temperatures ranging from 23 to 36°C. Bucks in the 1 st , 2 nd , 3 rd , and 4 th group were supplemented with 0, 50, 100 or 150 mg of Chinese royal jelly (RJ)/kg twice per week, respectively, over a 20-wk period. Semen quality and blood biochemical constituents were evaluated. RJ at any dose exhibited a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 24 publications
3
39
1
1
Order By: Relevance
“…Our results showed that there was a positive correlation between plasma testosterone and TSL. These results are in agreement with El-Hanoun et al (2014), who reported that a good relation between increased blood testosterone concentration and increase libido of male rabbits.…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that there was a positive correlation between plasma testosterone and TSL. These results are in agreement with El-Hanoun et al (2014), who reported that a good relation between increased blood testosterone concentration and increase libido of male rabbits.…”
Section: Discussionsupporting
confidence: 83%
“…In this respect, an improvement in total sexual libido (RT and STC) was reported in rabbit bucks treated with selenium plus vitamin E combination (Yassen et al,2016), royal jelly as natural active compounds (El-Hanoun et al, 2014), red algae (Ali and Mervat, 2013) or lycopene addition as natural antioxidants (Mangiagalli et al, 2012). The improvement in libido of treated bucks may be due to antioxidant components of S. platensis (Rezvanfar et al, 2008).…”
Section: Fig (1): Effect Of S Platensis Treatment On Sexual Desire mentioning
confidence: 94%
“…Also, the organic selenium, folic acid and their combination supplementation in rabbit feeds improved oxidative capacity in seminal plasma (Kamel, 2012). Treatment of bucks with royal jelly significantly increased TAC, GST, GPx, GSH and SOD, and significantly decreased TBARS in seminal plasma compared with control group (El-Hanoun et al, 2014). Mammalian sperm included rabbit display high rates of metabolic activity and are rich in polyunsaturated fatty acids rendering them particularly susceptible to ROS-induced oxidation (Castellini et al, 2006).…”
Section: Oxidative Capacity In Seminal Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Alleviating oxidative stress in rabbits includes the administration of antioxidants to supplement the endogenous antioxidants (Zeweil et al,2013;Simitzis et al, 2014;Trebušak et al, 2014), especially in thermal stress situations (El-Hanoun et al, 2014). Yeasts and their extracts are sources of natural antioxidants (Nishino and Ishikawa, 1998;Gazi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%